Induction of Silencing in Plants by High-Pressure Spraying of In vitro-Synthesized Small RNAs - Dalakouras, Athanasios; Wassenegger, Michèle; McMillan, John N.; Cardoza, Vinitha; Maegele, Ira; Dadami, Elena; Runne, Miriam; Krczal, Gabi; Wassenegger, Michael (Frontiers in Plant Science, 2016)
In this report we describe a method for the delivery of small interfering RNAs (siRNAs) into plant cells. In vitro synthesized siRNAs that were designed to target the coding region of a GREEN FLUORESCENT PROTEIN (GFP) transgene were applied by various methods onto GFP-expressing transgenic Nicotiana benthamiana plants to trigger RNA silencing. In contrast to mere siRNA applications, including spraying, syringe injection and infiltration of siRNAs that all failed to induce RNA silencing, high pressure spraying of siRNAs resulted in efficient local and systemic silencing of the GFP transgene, with comparable efficiency as was achieved with biolistic siRNA introduction. High-pressure spraying of siRNAs with sizes of 21, 22 and 24 nucleotides (nt) led to local GFP silencing. Small RNA deep sequencing revealed that no shearing of siRNAs was detectable by high-pressure spraying. Systemic silencing was basically detected upon spraying of 22 nt siRNAs. Local and systemic silencing developed faster and more extensively upon targeting the apical meristem than spraying of mature leaves.